The Effect of CPS Learning Model with CTL on Student Mathematical Learning Outcomes - Friska Belva Dwilestari (Universitas Islam Jember, 2019)
Learning is the main activity of the education process. The researcher compared the results of students' mathematics learning with conventional model learning models and used a combination of Creative Problem Solving (CPS) models with the Contextual Teaching Learning (CTL) approach to learning. Based on the results of the calculation of data analysis using dk (25) and the significance level (0.05), then obtained t_table (1.708). From the above calculation it is known that t count > t table (9.72> 1.708). Thus the working hypothesis () can be collected, and it can be said that learning with the Creative Problem Solving (CPS) model with Contextual Teaching Learning (CTL) influences the results of mathematics learning. The results of this study are also supported by the activities of teachers more motivating students on the importance of paying attention to and understanding the material taught and cooperation and responsibility for the success of a learning process Keywords: CPS, CTL, learning outcomes